Social-Media Analysis for Disaster Prevention: Forest Fire in Artenara and Valleseco, Canary Islands. - Zamarreño-Aramendia, Gorka; Cristofol, F. J.; De San Eugenio Vela, Jordi; Ginesta, Xavier (MPDI, 2020)
This manuscript investigates the use of social media, specifically Twitter, during the forest fires in Artenara and Valleseco, Canary Islands, Spain, during summer 2019. The used methodology was big-data analysis through the Union Metrics and Twlets tools, as well as content analysis of posts related to the fires written by seven relevant accounts on the days when the fires were active, which was between 17 August and 26 September, when 9636.40 hectares were burned. The accounts selected for analysis were the following: Ángel Víctor Torres, autonomous president; Canary Islands Government; Civil Protection of Las Palmas; Military Emergency Unit of the Spanish Army; Delegation of the Spanish Government in the Canary Islands; Citizen’s Service of the Canary Islands Government; and the information account of the Security and Emergency area of the Canary Islands Government. The study concludes that the Canary Islands authorities did not use social media as a preventive element, but almost exclusively as a live-information channel. Future recommendations are presented for the management of social media during natural disasters.
Keywords: Incendios forestales - Prevención y control; Redes sociales en Internet; Catástrofes naturales - Canarias; Canary Island; Natural disasters; Big data; Social media; Forest fire